Bioindicator Species in Climate Monitoring (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2025)
Bioindicator species -- organisms whose abundance, distribution, physiology, or phenology respond sensitively and predictably to specific environmental stressors -- are increasingly recognised as essential complements to physical climate sensors for monitoring the biological consequences of climate change at spatial resolutions and ecological timescales that instrument networks cannot achieve. This study systematically evaluated 247 candidate bioindicator species across six taxonomic groups (mammals, birds, reptiles, amphibians, fish, and invertebrates) for their effectiveness as climate change indicators across 38 long-term monitoring datasets from 24 countries spanning 1985-2023. Bioindicator effectiveness was quantified using five criteria: climate sensitivity (strength of correlation between species metric and climate variable), response lag (years between climate shift and detectable biological response), spatial resolution (area represented by a single monitoring point), monitoring cost-effectiveness (cost per unit of climate information), and multiple stressor confounding (degree to which non-climate stressors confound climate signal). Amphibians were the highest-scoring taxonomic group overall (mean composite bioindicator score = 7.84 +- 0.84 on a 1-10 scale), followed by freshwater invertebrates (7.24 +- 0.94) and breeding birds (6.84 +- 1.14). Phenological indicators -- breeding date, first appearance, and migration timing -- showed the fastest response lags (mean 0.8 +- 0.4 years) and highest climate sensitivity (mean r = 0.84 +- 0.08 with temperature) across taxonomic groups. A standardised bioindicator network design -- combining 14 priority species across six taxonomic groups with standardised monitoring protocols -- is proposed as a cost-effective complement to existing national climate monitoring systems, providing biological climate change fingerprinting at EUR 47,000 per monitoring site per year.